Variabilidade decadal da zona de convergência intertropical e sua influência na pluviosidade da região norte do Brasil - Andrade, Lene da Silva (2007)
The present work focused on the possible influence of the Pacific Decadal Oscillation (PDO) on the positioning and intensity of the Intertropical Convergence Zone (ITCZ) during its annual cycle over the Atlantic Ocean and its impact in the rainfall totals in the northern South American continent. For this purpose, the mean annual fields of outgoing longwave radiation (OLR), sea surface temperature (SST), omega (ω), meridional wind (V) and precipitation rate (P) of Reanalysis data sets (NCEP/NCAR) were analysed. In addition, observed rainfall monthly mean series (INMET and HIDROWEB), the University of Delawere (UDEL) rainfall, interpolated in a 0.5°x0.5° grid, and the PDO indices found in the NOAA/ESRL/PSD site were used to support the analyses. The results were visualized with applets available in the ESRL/PSD/NOAA s site as well as GrADS software. The records period 1948-2005 was divided into PDO cold phase (1948-1976), warm phase (1977- 1998) and current phase (1999-2005), which was used to verify the climate tendency of the last seven years. The results suggested that the ITCZ remained farther north of its mean position during the PDO cold phase. Apparently, the ascending branch of the Hadley Cell was displaced farther north and the descendent branch of the Walker Circulation positioned farther west of their normal positions. This pattern led to a rainfall reduction in parts of Amazonia. In the PDO cold phase, the normalized rainfall indices showed a more noticeable rainfall reduction (increase) western (eastern) of 52°W, in the State of Pará. In the PDO warm phase, opposite circulation patterns and higher climate variability were observed. The results suggested that the PDO, in general, modified the SST patterns in the Atlantic and, as a consequence, the positioning and intensity of the ITCZ. There are evidences that the PDO is experiencing a new cold phase. Thus, one expects that the ITCZ and the Amazonian rainfall present a similar behaviour of previous cold phase. Particular attention should be paid to the Brazilian States of Roraima and Maranhão, eastern Pará State and western Amazonas State, including Colombia, Venezuela e north-eastern Bolivia, that may experience a sensible rainfall reduction during the next 10 years. Another relevant result was relative to a possible enhancement of convection and rainfall over the southern Saharan region (Sahel), Africa, during the present PDO phase. It was noticed that it rained more in the region till 1975, when the SST anomalies of Equatorial Guinea Gulf were negative and the wind south component was stronger. These conditions seem to be returning.